Development of math efficacy scale for junior high school student in Indonesia - Kemas Rahmat Mubarrak; Helli Ihsan; Diah Zaleha Wyandini (Universitas Hamzanwadi, 2022)
Indonesian students are indicated to have a low math efficacy. Currently, no psychology scale has been created to measure the math efficacy of Indonesian students, especially for junior high school level students. This study aims to develop a math efficacy scale for junior high school level students or equivalent based on Indonesian students’ characteristics. The study used an exploratory sequential design with mixed methods. The results of qualitative analysis through focused group interviews on two small groups of eight students show that seven major themes were related to mathematics efficacy. Qualitative analysis as the basis for a scale development consisting of 33 items and is administered to 478 participants. The results of the quantitative analysis through validity test with Principal Component Analysis (PCA) shows that four dimensions appeared with total variance explained reaching 60.4%. The model was re-tested for compatibility with Confirmatory Factor Analysis (CFA) and obtained index values of p 0.001 (χ2), 0.047 (SRMR), 0.907 (TLI), 0.918 (CFI), and 0.064 (RMSEA). The four dimensions have met the standard of a fit index with 23 items remaining. The validity test was also supported by Pearson's Product Moment correlation of 0.795 for convergent validity test with Math Attitude Scale (MAS) and divergent validity test of -0.331 with Mathematical Self-Efficacy and Anxiety Questionnaire (MSEAQ). The scale's reliability was very good, with Cronbach's alpha value of 0.918.